Accompanying Students to a Free Public Intervention and Traumatis - Taty Fauzi; Nurbaiti Nurbaiti (Konselor, 2017)
Structuring the direction of national education brings learners ready to face the competition of global competition. Physical arrangement, the psychic's independence is continuously pursued. School counselors will continue to draw their duties and the nature altruistick attitude acts as a safety practitioner in dealing with cases - cases that occur in the school environment. Counselors as recruitment of competent and humanistic skills to support teaching philosophy that learners are given a role in the implementation of the curriculum. Teaching support, counselor to facilitator. To be a facilitator in the learning process skills possessed packed in one sense (sensitive, sympathetic, empathetic, altruistic). Humanistic counselor not possible to include constructivist instruction, either in the classroom or outside the classroom. School counselors are ready to get in on the issues of modern society (WTO, ASEAN, AFEC, AFTA, and MEA). The development of agrarian society that continues to erode into industrial society, impact on the lifestyle of learners How could materialize if the qualified graduates learners mentally shackled, depressed, causing the trauma of abuse in the mix, one in up bringing. Based on Act N0. 23 In 2002 the government explicitly states that every individual should have the opportunity to grow and develop, participate and, protection from discrimination. The reality often appears injustices and violations committed by unscrupulous teachers or peers. The government felt responsible and ensure that no children or learners received physical abuse, psychological